CD27+ microparticle interactions and immunoregulation of CD4+ T lymphocytes - Cagnet, Léonie; Neyrinck-Leglantier, Déborah; Tamagne, Marie; Berradhia, Lylia; Khelfa, Mehdi; Cleophax, Sabine; Pirenne, France; Vingert, Benoît (Frontiers in Immunology, 2023)
Aplasia and hematological malignancies are treated with platelet transfusions, which can have major immunomodulatory effects. Platelet concentrates (PCs) contain many immunomodulatory elements, including the platelets themselves, residual leukocytes, extracellular vesicles, such as microparticles (MPs), cytokines and other soluble elements. Two of these components, MPs and a soluble form of CD27 (sCD27), have been shown to play a particularly important role in immune system modulation. Indeed, the loss of CD27 expression is an irreversible marker of terminal effector CD3+ T-lymphocyte (TL) differentiation, and the CD27+ MPs present in PCs may maintain CD27 expression on the surface of TLs, and, thus, the activation of these cells. In this study, we phenotyped the CD27-expressing MPs present in PCs by microscale flow cytometry and investigated the interaction of these particles with CD4+ TLs. We cocultured MPs and PBMCs and determined the origin of the CD27 expressed on the surface of CD4+ TLs with the aid of two fluorochromes (BV510 for CD27 originating from MPs and BV786 for cellular CD27). We showed that the binding of CD27-expressing MPs involved the CD70 molecule, which was also present on these MPs. Finally, the maintenance of CD27 expression on the surface of TLs by sorted CD27+ MPs led to activation levels lower than those observed with other types of MPs. These results for CD27-expressing MPs and their CD70-mediated targeting open up new possibilities for immunotherapy based on the use of MPs to maintain a phenotype or to target immune cells, for example. Moreover, decreasing the levels of CD27-expressing MPs in transfused platelets might also increase the chances of success for anti-CD27 monoclonal immunotherapy.